MENAKAR SEJARAH TAFSIR MAQĀṢIDĪ - Zaenal Hamam; A. Halil Thahir (QOF, 2018)
This article elaborate the historical root of tafsir maqasidi through these steps:1) describing the four periods of the history of tafsir; 2) deducing points, from each period, which could provide an idea on the history of tafsir maqashidi, either theoretically or practically; 3) and providing examples of tafsir maqashidi. This article is done by documentation, by searching, reading, and reviewing qualitative data to be collected and analyzed by deductive method. The results of the article show: 1) historical roots of tafsir maqāṣidī have an intertwined with the history of tafsir in general, namely: marḥalat al-ta’sīs, marḥalat al-ta’ṣīl, marḥalat al-tafrī’, and marḥalat al-tajdīd. 2) among the points that can be explained related to the historical roots of tafsir maqaṣidī that is: a) in the ta’sīs period, there embryo maqāṣid al-sharī’ah. For example, there is a triple divorce in one majlis which is punishable by a single divorce at the time of the Prophet, during the time of Umar ra. punishable by three divorces, with consideration of ‘urf, for the benefit; b) in the tafrī’ period, born three maqāṣid alsharī’ah theories. first, al-Tūfī argues that the Shari’ah is none other than maṣlaḥah itself, so if naṣ is contrary to maṣlaḥah then take precedence of maṣlaḥah (‘alā sabīl al-takhṣīṣ); secondly, al-Gazalī states that “maṣlaḥah” is nothing but the Shari’a itself, so the theory of maṣlaḥah is taken inductively from naṣ; Third, al-Shāṭibī argues that maṣlaḥah and shari’a are one unity, so if naṣ that opposed to maṣlaḥah is qoṭ’ī al-dalālah, then naṣis precedence, and if naṣ that opposed to maṣlaḥah is dhannī al-dalālah, then maṣlaḥah is precedence; c) in the tajdīd period, classical maqāṣid concepts that are protection and preservation, altered by some contemporary Muslims such as Jasser Auda into a new concept of development and rights. The idea of contemporaryization of this terminology was then rejected by many fuqaha. 3) an example of the application of tafsir maqāṣidī is the interpretation of the Qur’an surah al-Nūr verse 2 in the context of the Unitary State of the Republic of Indonesia. In this case there is a ta’āruḍ between nas which enjoins the caning and “maṣlaḥah”. The application of the Islamic Criminal law in Indonesia to date has not received sufficient political support, so it will lead to greater mafsadah. Therefore, maṣlaḥah takes precedence and is made as takhṣīṣ above naṣ.